Human resources in the hotel industry of Serbia - Kordić, Nikolina; Milićević, Snežana (Hotel and Tourism Management, 2018)
Serbia is a country of significant but still insufficiently used tourist potential, uneven development of tourism, and a high concentration of tourist traffic. This implies a focus on a small number of tourist destinations that are commercially profiled. Serbia is characterized by a lack of a systematic approach to the development of tourism. This implies a lack of appropriate strategies that would adapt to specific areas, according to their attractiveness and specificities. It also implies inadequate human resources that should implement strategically set goals. It is necessary to define priorities, primarily in the area of profiling the material basis of tourism, i.e. the offer of accommodation facilities. It is necessary to provide adequate personnel, whose activity will be a key factor in the further development of tourism and hotel industry of Serbia. The aim of this paper is to look at and analyze the basic characteristics of employment in the hotel industry of Serbia, primarily the volume and dynamics of the employees in the hotel industry and their qualification structure, in order to identify the key weaknesses and to point out the ways for their overcoming. Secondary statistical data were used in this context and the analytical-synthetic method was applied. As shown in this paper, positive shifts in improving human resources in the hotel industry of Serbia are evident. A further improvement of human resources in the hotel industry of Serbia should be guided by global trends, in order to encourage a further improvement of the quality of the hotel industry in Serbia as a tourist destination.